Disaster-Resilient Village Governance: A Public Administration Perspective on Social-Ecological Reselience - Rutiana Dwi Wahyunengseh; Dewi Bayu Pamungkas (Jurnal Ilmu Lingkungan, 2025)
Society faces significant threats from external disruptions, particularly natural disasters, which impact both people and ecosystems. These disturbances require social-ecological systems to self-regulate and adapt to changing conditions. However, efforts to develop a comprehensive understanding of social-ecological resilience remain insufficient. To effectively grasp the dynamics and capacity of resilience, empirical studies are essential. Most research on this topic focuses on urban areas, often neglecting the unique conditions of rural communities. This study aims to assess rural resilience through the lens of social-ecological systems. Natural disasters progress through four key stages: pre-disaster preparedness, crisis management, post-disaster recovery, and learning for future resilience. Using qualitative methods, including interviews and focus group discussions, this research was conducted in Kutamendala Village, Brebes Regency. Findings reveal that resilience in disaster-prone villages can be strengthened through structured preparedness and continuous learning. The community demonstrated awareness of disaster risks and actively participated in risk reduction efforts rather than relying solely on external aid. Decentralized coordination allowed for effective disaster response, while post-disaster recovery efforts involved collaboration across sectors, improving infrastructure and essential services. Additionally, inclusive and sustainable learning initiatives were implemented, reinforcing long-term preparedness and strengthening the village’s ability to withstand future disasters.